An Ethanolic Extract of Cucurbita pepo L. Seeds Modifies Neuroendocrine Disruption in Chronic Stressed Rats and Adrenal Expression of Inflammatory Markers and HSP70 - Almohaimeed, Hailah M.; Hamed, Shereen; Seleem, Hanan S.; Batawi, Ashwaq H.; Mohammedsaleh, Zuhair M.; Balgoon, Maha Jameal; Ali, Soad S.; Al Jaouni, Soad; Ayuob, Nasra (Frontiers in Pharmacology, 2021)
Background: Pumpkin (Cucurbita pepo L.) was described to have antioxidant, anti-inflammatory, anti-fatigue and antidepressant-like effect. The adrenal gland is an important stress-responsive organ that maintains homeostasis during stress. Objectives: This study aimed to assess the effect of the administration of Cucurbita pepo L. (CP) extract on relieving the chronic unpredictable mild stress (CUMS)-induced behavioral and biochemical effect as well as its impact on the structure of the adrenal gland and explore the mechanism behind this impact. Materials and methods: Forty male albino rats divided in 4 groups (n=10); control, CUMS, Fluoxetine-treated and CP-treated groups. Behavioral changes, corticosterone level pro-inflammatory cytokines TNF-α, IL-6 and oxidant/antioxidant profile were assessed in the serum at the end of the experiment. Adrenal glands were processed for histopathological and immunohistochemical assessment. Gene expression of Caspase-3, Ki67 and heat shock protein 70 (HSP70) were assessed in adrenal glands using-PCR. Results: CP extract significantly reduced corticosterone level (p<0.001), immobility time (p<0.001), inflammatory and oxidative changes associated with CUMS-induced depression compared to the untreated group. CP extract alleviated CUMS-induced adrenal histopathological changes and significantly reduced (p<0.001) apoptosis and significantly up-regulated antioxidants levels in the serum. Conclusion: Cucurbita pepo L. effectively ameliorated the chronic stress-induced behavioral, biochemical as well as adrenal structural changes mostly through its antioxidant and anti-inflammatory effect.